2019
DOI: 10.1002/adfm.201808375
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Manganese Dissolution in Potassium Manganate with Rich Oxygen Defects Engaged High‐Energy‐Density and Durable Aqueous Zinc‐Ion Battery

Abstract: The manganese dissolution leading to sharp capacity decline as well as the sluggish reaction kinetic are still major issues for manganese‐based materials as aqueous zinc‐ion batteries (ZIBs) cathodes. Here, a potassium‐ion‐stabilized and oxygen‐defect K0.8Mn8O16 is reported as a high‐energy‐density and durable cathode for neutral aqueous ZIBs. A new insight into suppressing manganese dissolution via incorporation of K+ ions to intrinsically stabilize the Mn‐based cathodes is provided. A comprehensive study sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
426
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 629 publications
(458 citation statements)
references
References 50 publications
20
426
0
Order By: Relevance
“…In addition, Fang et al reported an oxygen‐deficient potassium manganate (K 0.8 Mn 8 O 16 ) with potassium ions stably inserted into the tunnel cavity as high activity cathode for Zn‐ion batteries. This work showed that oxygen defects promoted the conductivity and opened the polyhedron walls of MnO 6 for facilitating ion diffusion in the ab ‐plane, which was beneficial to accelerate the reaction kinetics and improve the capacity of K 0.8 Mn 8 O 16 (Figure d) …”
Section: Defect Engineering On Electrode Materialsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, Fang et al reported an oxygen‐deficient potassium manganate (K 0.8 Mn 8 O 16 ) with potassium ions stably inserted into the tunnel cavity as high activity cathode for Zn‐ion batteries. This work showed that oxygen defects promoted the conductivity and opened the polyhedron walls of MnO 6 for facilitating ion diffusion in the ab ‐plane, which was beneficial to accelerate the reaction kinetics and improve the capacity of K 0.8 Mn 8 O 16 (Figure d) …”
Section: Defect Engineering On Electrode Materialsmentioning
confidence: 88%
“…d) Schematic diagram of hydrogen ions diffusion into K 0.8 Mn 8 O 16 with perfect structure and oxygen‐defect structure. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Defect Engineering On Electrode Materialsmentioning
confidence: 99%
“…In this regard, metallic zinc (Zn) has been considered to be one of the alternatives due to its low potential (−0.762 V vs standard hydrogen electrode (SHE)), high theoretical capacity (820 mAh g −1 ), large abundance, environmental‐friendly properties, and inherent safety 7–9. Up to now, various Zn‐based batteries have been widely investigated, such as Zn–air battery,10–13 Zn–NiOOH battery,14–16 Zn–V 2 O 5 battery,17–19 Zn–MnO 2 battery,20–23 etc. However, besides the dendrite growth in the electrolyte, the Zn anode corrosion and the formation of ZnO densification on the Zn electrode surface have become the challenges for the development of rechargeable Zn‐based batteries, which would result in poor reversibility, low Coulombic efficiency (CE), and the decayed capacity 24.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that structural transformation of α‐MnO 2 cathode during cycling is reversible. Lately, Liang et al reported a new understanding for H + ‐storage mechanism that the diffusion of H + into K 0.8 Mn 8 O 16 host results in simultaneous insertion (H x K 0.8 Mn 8 O 16 ) and conversion (MnOOH or K 0.1 MnOOH) reaction. Interestingly, the similar phenomena are also observed in the α‐MnO 2 electrode.…”
Section: Manganese‐based Oxidesmentioning
confidence: 99%
“…Cations and H 2 O molecules could be embedded in its tunnels to form M 1 ± x Mn 6 O 12 ·3‐4H 2 O (M = Na, Ca, Mg, Ba, K etc. ), which keep the structure stable . For example, todorokite‐type MnO 2 with embedded Mg 2+ and water molecules (Mg 1.8 Mn 6 O 12 ·4.8H 2 O) was constructed as cathode in aqueous ZIBs .…”
Section: Manganese‐based Oxidesmentioning
confidence: 99%